Corporate Governance, Ukuran Perusahaan, Asimetri Informasi dan Manajemen Laba - Wibowo, Adelphia Christian; Sari, Maria Mediatrix Ratna (E-Jurnal Akuntansi; Vol 32 No 2 (2022), 2022)
The research was conducted with the aim of finding empirical evidence regarding earnings management that is influenced by corporate governance, firm size and information asymmetry. The study involved 100 manufacturing companies listed on the Indonesia Stock Exchange in 2017-2019 with 300 samples of observation. The results of the research analysis found that the presence of women on the board of directors, commissioners and audit committees has not been able to minimize earnings management practices. The larger the size of a company and the information asymmetry that occurs, the greater the possibility of earnings management practices carried out by the company. Keywords: Corporate Governance; Company Size; Information Asymmetry; Earnings Management.